2010
DOI: 10.1167/iovs.09-4383
|View full text |Cite
|
Sign up to set email alerts
|

Choroidal Thickness in Healthy Japanese Subjects

Abstract: Purpose. To study posterior choroidal thickness and its profile based on location in healthy Japanese subjects and the correlation with axial length, refractive error (RE), and age. Methods. Eighty-six eyes of 43 healthy volunteers with no ophthalmic or systemic symptoms were examined with prototype high-penetration optical coherence tomography using a 1060-nm light source. Eyes with high myopia (exceeding -6 D) or with retinal/choroidal disease were excluded. The spherical equivalent RE was measured by autore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

85
469
22
4

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 590 publications
(580 citation statements)
references
References 22 publications
85
469
22
4
Order By: Relevance
“…Figure 4 shows EDI-OCT images of the choroid of 1 eye with CRVO before and after intravitreal bevacizumab treatment. 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 and 222.6 μm, respectively) in our study was less than that in the previous study, 20 this difference between the studies may have been caused by differences in the measurement software, the OCT light source, the patient profile (e.g., age). Maruko et al 3,4 performed ICGA and found that subfoveal choroidal thickness in the fellow eyes of patients with central serous chorioretinopathy was increased in the eyes with choroidal vascular hyperpermeability.…”
Section: Resultscontrasting
confidence: 73%
“…Figure 4 shows EDI-OCT images of the choroid of 1 eye with CRVO before and after intravitreal bevacizumab treatment. 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 and 222.6 μm, respectively) in our study was less than that in the previous study, 20 this difference between the studies may have been caused by differences in the measurement software, the OCT light source, the patient profile (e.g., age). Maruko et al 3,4 performed ICGA and found that subfoveal choroidal thickness in the fellow eyes of patients with central serous chorioretinopathy was increased in the eyes with choroidal vascular hyperpermeability.…”
Section: Resultscontrasting
confidence: 73%
“…The mean subfoveal choroidal thickness reported has varied between studies from 225m (SD 53m), 23 to 354nm (SD 111m). 28 The control group employed in our study was found to have a slightly lower mean subfoveal choroidal thickness of 213m (SD 63m), which may reflect the greater mean age of the participants than in most previous studies.…”
Section: Discussionmentioning
confidence: 52%
“…Multiple studies have assessed choroidal thickness in healthy individuals using the OCT, [23][24][27][28][29][30] however, only a few have used a 1060nm system. [27][28] A recent study using 1060nm OCT to investigate the correlation between axial length and choroidal thickness in 34 healthy subjects (64 eyes) aged 19-80 years, found a mean central choroidal thickness of 315m (SD 106m), with the choroid thinnest in the nasal parafovea.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2 Several recent studies using commercially available and custom-developed Fourier-domain EDI-OCT have afforded new insights into the in vivo structural characteristics of the normal adult human choroid. [3][4][5][6] The average choroidal thickness in the subfoveal region of healthy adults (over 18 years of age) is 192-354 mm. Thickening of the choroid may be mechanistically linked to the synthesis of scleral macromolecules, and thus may have important roles in the homeostatic control of eye growth and the etiologies of myopia and hyperopia.…”
Section: Introductionmentioning
confidence: 99%